Policy to Expand Accessing Antimalarial Drug Treatment in Papua Region-Indonesia: Who Should Be the Target? - Yuneu Yuliasih; Mara Ipa; Agung Dwi Laksono; Anis Nur Widayati; Nita Rahayu; Endang Puji Astuti (Indian Journal of Public Health)
The Papua region of Indonesia faces a substantial burden of malaria cases. To broaden the understanding of factors influencing access to antimalarial drug treatment, researchers analyzed the 2018 Indonesia Basic Health Survey data. Their examination encompassed demographics, socioeconomic elements, and transportation expenses. Notably, the study revealed that Papuan malaria patients in West Papua were 1.812 times more likely to receive anti-malarial drug treatment compared to those in Papua Province. In addition, individuals residing in rural areas and those not engaged in farming were more inclined to access treatment. Surprisingly, education level did not correlate with treatment accessibility, while individuals with higher wealth were less likely to receive treatment. Moreover, transportation costs did not pose a barrier to treatment access. The study underscores the importance of targeting specific demographics, including those in Papua Province, urban areas, and nonfarming occupations, to enhance the availability of anti-malarial treatment in the region.